Blueberry and/or Banana Consumption Mitigate Arachidonic, Cytochrome P450 Oxylipin Generation During Recovery From 75-Km Cycling: A Randomized Trial - Nieman, David C.; Gillitt, Nicholas D.; Chen, Guan-Yuan; Zhang, Qibin; Sha, Wei; Kay, Colin D.; Chandra, Preeti; Kay, Kristine L.; Lila, Mary Ann (Frontiers in Nutrition, 2020)
Oxylipins are bioactive lipid oxidation products, have vital regulatory roles in numerous physiological processes including inflammation, and can be impacted by diet. This study determined if 2-weeks of blueberry and/or acute banana ingestion influenced generation of n-6 and n-3 PUFA-derived oxylipins during recovery from exercise-induced physiological stress. Cyclists (n=59, 39±2 years of age) were randomized to freeze-dried blueberry or placebo groups, and ingested 26 grams/d (1 cup/d blueberries equivalent) for 2 weeks. Cyclists reported to the lab in an overnight fasted state and engaged in a 75-km cycling time trial (185.5±5.2 min). Cyclists from each group (blueberry, placebo) were further randomized to ingestion of a water-only control or water with a carbohydrate source (Cavendish bananas, 0.2 g/kg carbohydrate every 15 minutes) during exercise. Blood samples were collected pre- and post-2-weeks blueberry supplementation, and 0 h-, 1.5 h-, 3 h-, 5 h-, 24 h-, 48 h-post-exercise. Plasma oxylipins and blueberry and banana metabolites were measured with UPLC–tandem MS/MS. Significant time by treatment effects (8 time points, 4 groups) were found for 24 blueberry- and 7 banana-derived phenolic metabolites in plasma (FDR adjusted p-values<0.05). Significant post-exercise increases were observed for 64 of 67 identified plasma oxylipins. When oxylipins were grouped relative to fatty acid substrate [arachidonic acid (ARA), eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), α-linolenic acid (ALA), linoleic acid (LA)], and enzyme systems [cytochrome P450 (CYP), lipoxygenase (LOX)], banana and blueberry ingestion were independently associated with significant post-exercise reductions in pro-inflammatory ARA-CYP hydroxy- and dihydroxy-eicosatetraenoic acids (HETEs, DiHETrEs) (treatment effects, FDR adjusted p-values<0.05). These trial differences were especially apparent within the first three hours of recovery. In summary, heavy exertion evoked a transient but robust increase in plasma levels of oxylipins in cyclists, with a strong attenuation effect linked to both chronic blueberry and acute banana intake on proinflammatory ARA-CYP oxylipins.